(untitled) (Acta Scientiarum. Language and Culture, 2025)
Education is an international human right and a condition for the free development of peoples and individualities. Therefore, reading should also be recognized as a human right, as it is a structural element in the process of humanizing individuals and a condition for appropriating humanity’s cultural, theoretical, and scientific heritage. During the COVID-19 pandemic, schools in Brazil and worldwide had to adopt new pedagogical strategies and restructure those previously used, including reading practices. Thus, a question arises: what reading practices were implemented during the COVID-19 pandemic by Children’s School teachers to form readers? This study is based on scientific papers in the Education field published between 2020 and 2022 and aims to identify the reading practices implemented by Children’s School (0 to 10 years old) teachers in Latin American countries during the COVID-19 pandemic. This is a bibliographical research with a qualitative data analysis, using a critical-dialectical approach. Although the results are still incipient, the following practices were identified: the use of diverse literary genres, pleasure reading, reading of literary texts, discussions via WhatsApp, storytelling via Google Meet, and broadcasting on Facebook. Furthermore, given the lack of scientific works on this subject, new research is essential to understand the reading practices employed during this period, in an attempt to understand the challenges faced and develop strategies for the post-pandemic context.